Banking on Women Leaders : A Case for More? - Sahay, Ratna; Barajas, Adolfo; Cihak, Martin; N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2017)
Using a new dataset, we measure the large gap between the representation of men and women in leadership positions in banks and bank supervision agencies worldwide. Women occupied less than 2 percent of bank CEOs positions, and less than 20 percent of the board seats in more than 80 percent of the observations across banks over time. Contrary to common perceptions, many low- and middle-income countries have a higher share of women in bank boards and banking supervision agency boards compared to advanced economies. Econometric analysis suggests that, controlling for relevant bank and country-specific factors, the presence of women as well as a higher share of women on bank boards is associated with greater bank stability, as represented by higher z-scores and lower nonperforming loan ratios. We also examine the share of women on boards of banking supervision agencies by compiling a new dataset. We find that it is associated with greater bank stability. Further research is needed to identify specific mechanisms through which these stability benefits are achieved, and to understand the conditions that have facilitated entry of women into leadership roles in banks and supervision agencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet